2022
DOI: 10.1021/acs.nanolett.2c00820
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Free Layered Semiconductors for 2D Transistors with On-State Current Density Exceeding 1.3 mA μm–1

Abstract: High-mobility and air-stable two-dimensional (2D) Bi 2 O 2 Se semiconductor holds promise as an alternative fast channel material for next-generation transistors. However, one of the key challenges remaining in 2D Bi 2 O 2 Se is to prepare high-quality crystals to fabricate the high-performance transistors with a high on-state current density. Here, we present the free-standing growth of strainfree 2D Bi 2 O 2 Se crystals. An ultrahigh Hall mobility of 160 000 cm 2 V −1 s −1 is measured in strain-free Bi 2 O 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Very recently, Tan et al reported that the on-stable current density in strain-free 2D Bi 2 O 2 Se transistors can reach a very high value of exceeding 1.3 mA μm −1 . 20 Specifically, Bi 2 O 2 Se has a unique Si-like property that can be self-oxidized into a dense, conformal, and high-κ native oxide Bi 2 SeO 5 21 which can directly serve as a gate insulator on top of a highmobility channel. A series of meaningful works to uncover the intriguing physical properties of Bi 2 O 2 Se were reported consecutively, such as ferroelectricity, 13,16 carrier-density-insensitive high mobility, 18,22 surface Se−Se dimers 11 and Josephson junction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Tan et al reported that the on-stable current density in strain-free 2D Bi 2 O 2 Se transistors can reach a very high value of exceeding 1.3 mA μm −1 . 20 Specifically, Bi 2 O 2 Se has a unique Si-like property that can be self-oxidized into a dense, conformal, and high-κ native oxide Bi 2 SeO 5 21 which can directly serve as a gate insulator on top of a highmobility channel. A series of meaningful works to uncover the intriguing physical properties of Bi 2 O 2 Se were reported consecutively, such as ferroelectricity, 13,16 carrier-density-insensitive high mobility, 18,22 surface Se−Se dimers 11 and Josephson junction.…”
mentioning
confidence: 99%
“…Two-dimensional Bi 2 O 2 Se was fabricated into ultrafast, highly sensitive infrared photodetectors and high-speed field-effect transistors. Very recently, Tan et al reported that the on-stable current density in strain-free 2D Bi 2 O 2 Se transistors can reach a very high value of exceeding 1.3 mA μm –1 . Specifically, Bi 2 O 2 Se has a unique Si-like property that can be self-oxidized into a dense, conformal, and high-κ native oxide Bi 2 SeO 5 which can directly serve as a gate insulator on top of a high-mobility channel.…”
mentioning
confidence: 99%
“…The high contact resistance becomes a bottleneck for the application of 2D materials to FETs. To date, numerous efforts have been made to address this problem, such as the following: decreasing the Schottky barrier height of the metal/semiconductor junction with suitable work function metals; achieving Fermi-level pinning through inserting an insulating tunneling layer between the metal and the semiconductor; , designing contact geometry; phasing engineering a 2D semiconductor into a metallic phase; , and molecular and electrolyte doping of the channel. , Consider the most extensively researched material, MoS 2 , as an example. Leong et al reported that the contact resistance of MoS 2 /nickel-etched-graphene can be reduced to 200 Ω·μm .…”
Section: Introductionmentioning
confidence: 99%
“…BOS is a layered semiconductor, deemed as a highly competitive material for next-generation electronics [25] and optoelectronics [26][27][28] , on account of environment stability, high mobility and robust band gap ( = 0.8 eV) [25] . The room temperature (room-T ) Hall mobility µ H is up to 450 -500 cm 2 .V −1 .s −1 [25] and low-T µ H is larger than 10 5 cm 2 .V −1 .s −1 [29] , surpassing that of MoS 2 [30,31] . For BOS transistors, the on-state current density amounts to 1.3 mA µm −1 [29] with the leakage current below 0.015 A cm −2 , fulfilling the criteria of low-power HP electronic devices in the International Roadmap for Devices and Systems (IRDS) [32] .…”
Section: Introductionmentioning
confidence: 99%
“…The room temperature (room-T ) Hall mobility µ H is up to 450 -500 cm 2 .V −1 .s −1 [25] and low-T µ H is larger than 10 5 cm 2 .V −1 .s −1 [29] , surpassing that of MoS 2 [30,31] . For BOS transistors, the on-state current density amounts to 1.3 mA µm −1 [29] with the leakage current below 0.015 A cm −2 , fulfilling the criteria of low-power HP electronic devices in the International Roadmap for Devices and Systems (IRDS) [32] .…”
Section: Introductionmentioning
confidence: 99%